2020
DOI: 10.3390/mi11020177
|View full text |Cite
|
Sign up to set email alerts
|

An LED-Driven AuNPs-PDMS Microfluidic Chip and Integrated Device for the Detection of Digital Loop-Mediated Isothermal DNA Amplification

Abstract: The sensitive quantification of low-abundance nucleic acids holds importance for a range of clinical applications and biological studies. In this study, we describe a facile microfluidic chip for absolute DNA quantifications based on the digital loop-mediated isothermal amplification (digital LAMP) method. This microfluidic chip integrates a cross-flow channel for droplet generation with a micro-cavity for droplet tiling. DNA templates in the LAMP reagent were divided into ~20,000 water-in-oil droplets at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…2a, AuNRs were synthesized according to the seed-mediated growth method, modified with silica, and then dispersed in ethanol. 32 Then the AuNR-ethanol was mixed with the PDMS prepolymer and finally evaporated at 65 °C for 3 h to remove ethanol and obtain pure AuNR-PDMS. In this study, the modified silica shell can improve the dispersion of AuNRs in ethanol and PDMS and the stability under irradiation.…”
Section: Design and Preparation Of The Microfluidic Chipmentioning
confidence: 99%
See 1 more Smart Citation
“…2a, AuNRs were synthesized according to the seed-mediated growth method, modified with silica, and then dispersed in ethanol. 32 Then the AuNR-ethanol was mixed with the PDMS prepolymer and finally evaporated at 65 °C for 3 h to remove ethanol and obtain pure AuNR-PDMS. In this study, the modified silica shell can improve the dispersion of AuNRs in ethanol and PDMS and the stability under irradiation.…”
Section: Design and Preparation Of The Microfluidic Chipmentioning
confidence: 99%
“…At present, studies have shown that a modified disposable syringe unit 50 and a cheap LED 21,32 can be used for CF-PCR liquid driving and plasmonic PCR heating, leaving room for further cost reduction and miniaturization. We will build on this paper by integrating these cheaper and smaller components and developing a fully automated fluorescence analysis application on a smartphone to bring this study closer to point-of-care testing (POCT).…”
Section: Comprehensive Characterization Of the Systemmentioning
confidence: 99%
“…Owing to this property, photothermal materials, such as gold, silver, and copper nanoparticles can be used as heaters for nucleic acid amplication. [32][33][34] To generate heat from photothermal materials, an optical device that can provide light radiation of a specic wavelength is required.…”
Section: Introductionmentioning
confidence: 99%
“…Although AuNPs significantly improve the quality of PCR reaction by heat transfer enhancement, they may have an inhibitory effect on nucleic acid amplification at high concentrations 48 , 49 . Besides, photothermal heating using AuNPs suffers from a nonuniform distribution of nanoparticles 50 . AuNFs may be regarded as a better alternative for nucleic acid amplification than AuNPs.…”
Section: Introductionmentioning
confidence: 99%